Beliefs on sex differences and practices in the family - Poeschl, Gabrielle (2001)
The access of women to the professional world did not significantly alter the traditional roles in the family. Women still perform most of the domestic work and have less power than men in decisions that are relevant to family life. Not withstanding these facts, several studies indicate that men and women appear to be satisfied with social practices in the family. In order to further understand the obstacles to change in family roles, 418 teachers of both sexes (aged 24-70 yrs) participated in a study which analyzed the effects of beliefs about sex differences on the perception and judgments of different patterns of family organization, as well as the actors adopting these patterns. Results show that, although men and women consider the equalitarian couple as an ideal one, beliefs about sex differences contribute to more positive judgments of the traditional division of roles and more negative judgments of the equalitarian male actor. According to these results, resistances toward change in family roles can be explained by the persistence of beliefs about sex differences that are largely shared by both men and women.  DOI: http://dx.doi.org/10.17575/rpsicol.v15i1.492